1977
DOI: 10.2307/1540724
|View full text |Cite
|
Sign up to set email alerts
|

INTRACELLULAR CRYSTAL-BEARING VESICLES IN THE EPIDERMIS OF SCLERACTINIAN CORALS,ASTRANGIA DANAE(AGASSIZ) ANDPORITES PORITES(PALLAS)

Abstract: Orthorhombic aragonitic crystals, embedded with a granular lipo-protein matrix and surrounded by a trilaminar membrane, are localized in the apical cytoplasm of epidermal cells of Scleractinian corals. Adult specimens of Astrangia danae (Agassiz) and settled planulae of Porites porites (Pallas) contain crystals averaging 0.7 mu by 0.1 mu by 0.3 mu within Golgi-derived vesicles. Short-term labelling with 45Ca reveals distribution of radioactivity amont a basic tissue fraction (92%) an acid tissue fraction (5%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…If the Ca is associated with mucus granules of some sort and not with the 250 nm vesicles, as envisaged by Hayes and Goreau (1977), or with the small 50 nm vesicles as suggested by Johnston (1980), then the mucus and its associated Ca could still function in some similar manner to that proposed by Goreau (1959). Goreau suggested that Ca 2ϩ was "absorbed" on a polyanionic mucopolysaccharide (Goreau, 1956) in the organic matrix, where it subsequently combined with HCO 3 Ϫ to form calcium carbonate.…”
Section: Calcificationmentioning
confidence: 97%
See 1 more Smart Citation
“…If the Ca is associated with mucus granules of some sort and not with the 250 nm vesicles, as envisaged by Hayes and Goreau (1977), or with the small 50 nm vesicles as suggested by Johnston (1980), then the mucus and its associated Ca could still function in some similar manner to that proposed by Goreau (1959). Goreau suggested that Ca 2ϩ was "absorbed" on a polyanionic mucopolysaccharide (Goreau, 1956) in the organic matrix, where it subsequently combined with HCO 3 Ϫ to form calcium carbonate.…”
Section: Calcificationmentioning
confidence: 97%
“…In support of this hypothesis Johnston refers to preliminary experiments on the histochemical detection of Ca in intercellular spaces in all cell layers by precipitation with sodium fluoride, except at the apical regions of the intercellular spaces in the calicoblastic ectoderm and in the subskeletal space. Hayes and Goreau (1977) and Goreau and Hayes (1977) found that the large vesicles in the calicoblastic ectodermal cells contained electron-lucent crystals. They argued that these were calcium carbonate crystals embedded in an organic matrix and suggested that these formed the initial sites for nucleation catalysis, calcium carbonate being subsequently precipitated on these primary crystals from the fluid in the subskeletal space to form crystals growing by epitaxy.…”
Section: Calcificationmentioning
confidence: 98%
“…The high carbonic anhydrase levels predicted have been found (1,5,8). The increase of alkalinity stimulates supersaturation and catalyzes nucleation of calcium carbonate (7). Marshall suggests that carbonate ion removal by calcification releases CO2 for photosynthesis, which would make carbonic anhydrase superfluous and drive cellular pH acidic.…”
mentioning
confidence: 95%
“…The gastroendodermal cells of hermatypic hard corals host symbiotic zooxanthellae (unicellular algae evolved from free-living dinoflagellates of the gymnodinioid form, Symbiodinium sp.). In vivo histochemical and ultrastructural observations of calcifying apical branches of hard coral (13,14), and on radiochemical studies of 45 Ca 2ϩ incorporation into the skeleton (15), have shown that calcification takes place in the calicoblastic epidermis. Autotrophic zooxanthellae symbionts provide part of the coral nutrients and their activity facilitates calcification (16).…”
mentioning
confidence: 99%